Peripheral Nerve Magnetoneurography With Optically Pumped Magnetometers - Bu, Yifeng; Prince, Jacob; Mojtahed, Hamed; Kimball, Donald; Shah, Vishal; Coleman, Todd; Sarkar, Mahasweta; Rao, Ramesh; Huang, Mingxiong; Schwindt, Peter; Borna, Amir; Lerman, Imanuel (Frontiers in Physiology, 2022)
Electrodiagnosis is routinely integrated into clinical neurophysiology practice for peripheral nerve disease diagnoses such as neuropathy, demyelinating disorders, nerve entrapment/impingement, plexopathy or radiculopathy. Measured with conventional surface electrodes, the propagation of peripheral nerve action potentials along a nerve is the result of ionic current flow which, according to Ampere’s Law, generates a small magnetic field that is also detected as an “action current” by magnetometers such as superconducting quantum interference device (SQUID) Magnetoencephalography (MEG) systems. Optically pumped magnetometers (OPMs) are an emerging class of quantum magnetic sensors with a demonstrated sensitivity at the 1 fT/√Hz level, capable of cortical action current detection. But, OPMs were ostensibly constrained to low bandwidth therefore precluding their use in peripheral nerve electrodiagnosis. With careful OPM bandwidth characterization, we hypothesized OPMs may also detect compound action current signatures consistent with both Sensory Nerve Action Potential (SNAP) and the Hoffmann Reflex (H-Reflex). In as much, our work confirms OPMs enabled with expanded bandwidth can detect the magnetic signature of both the SNAP and H-Reflex. Taken together, OPMs now show potential as an emerging electrodiagnostic tool.